Psychology of language a critical introduction - Forrester, Michael A.; Sage eBooks (London : SAGE, 1996)
'Psychology of Language' examines both the formal/structural aspects of linguistics and psycholinguistics and the concerns of sociolinguistics, conversation analysis, and social semiotics. Author Michael A. Forrester discusses three levels of communication: thinking - the cognitive processes of self-communication; talk - with an emphasis on everyday conversational behaviour; text - including the study of reading and writing. Within these areas, Forrester introduces a wide range of subjects, from language structure, semantics, and deixis to conversation, power relations in language, interpretation, and postmodern psychology.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Psycholinguistics; Electronic books